Study of Internal Flow in a Liquid Nitrogen Flow Decelerator Through Swirl Effect Consisting of a Jet-Type Cryogenic Injection System for Food Freezing - Arriaga, Ian (2024)
This article addresses the study of internal flow dynamics within a cryogenic chamber designed for freezing food using liquid nitrogen injection. The chamber features a circular section with strategically placed jet-type atomizers for this purpose. The primary objective is to extend the residence time of the cryogenic fluid within the chamber to ensure uniform and effective freezing of the passing food items. This is achieved by inducing a swirl effect through strategic deceleration of the flow using the atomizers. The meticulous placement of these atomizers at periodic intervals along the internal walls of the cylindrical chamber ensures prolonged recirculation of the internal flow. Internal temperature analysis is crucial to ensure the freezing process. The study is supported by numerical analysis in CFD ANSYS to assess the dynamics of the swirl effect and parameters associated with the nitrogen–air interface, from which we obtain a sophisticated analysis thanks to the design of a hexahedral mesh made in greater detail in ICEM CFD. This approach aims to understand internal flow behavior and its correlation with the complexity of cryogenic system design, utilizing variable nitrogen-injection pressures and strategic atomizer placement as fundamental parameters to optimize system design.